Effects of three epoxides--ethylene oxide, propylene oxide and epichlorohydrin--on cell cycle progression and cell death in human diploid fibroblasts - Mlejnek, P; Kolman, A (Chemico-biological interactions, 1999)
Ethylene oxide (EtO), propylene oxide (PO), and epichlorohydrin (ECH) strongly influenced the G1/S progression in human diploid fibroblasts, VH-10. However, these epoxides did not affect substantially the G2/M progression. It was found that G1 arrest is induced by these epoxides 6-18 h after the treatment at doses above 5, 3, and 0.5 mMh for EtO, PO, and ECH, respectively. An inhibitory effect on DNA synthesis was also demonstrated at the same doses within the same time interval. On the contrary, the epoxides transiently stimulated DNA synthesis 3-18 h after the treatment with the lower doses (below 5, 3, and 0.5 mMh for EtO, PO, and ECH, respectively). This effect was manifested both as an elevated rate of DNA synthesis and as an increase in the number of cells in S-phase. Among the three studied epoxides EtO was the most effective one: the increases of the rate of DNA synthesis and of cells in S-phase were 35 and 55%, respectively. All the epoxides tested induced significant decrease of intracellular level of reduced glutathione (GSH) shortly after cell exposure. While low and moderate doses induced a transient decrease in GSH level the high doses induced its irreversible depletion. The extensive GSH depletion was related to cell death. Morphological examination of cell nuclei indicated that epoxide-treated cells die via necrosis. This conclusion is supported by the lack of such features of the apoptosis as chromatin condensation and the occurrence of so called 'apoptotic bodies'. The absence of nucleosomal fragmentation of DNA and an increase of the permeability of the plasma membrane after the epoxide treatment also indicated a necrotic form of cell death. ECH is about ten times more toxic than the two other epoxides, and it causes almost 100% necrosis at dose of 3.0 mMh.
Keywords: DNA Fragmentation; Male; diploidie; Epichlorohydrin; replikace DNA; epoxidové sloučeniny; Diploidy; DNA Replication; fibroblasty; Humans; fragmentace DNA; Ethylene Oxide; ethylenoxid; mužské pohlaví; glutathion; buněčný cyklus; Cell Line; Cell Cycle; Epoxy Compounds; DNA; buněčná smrt; Glutathione; Cell Death; lidé; Fibroblasts; epichlorhydrin; buněčné linie